Some features of the expert diagnostic system application for truble schooting a gas-turbine engine in the process of its operation - Чоха, Ю. М. (Proceedings of National Aviation University (archive), 2021)
The present stade of the problem of the aircraft gas-turbine engines operation is considered. Shortcomings of the methods and techniques applied for their diagnosis are determinated and an inference about the perfectiveness of the expert diagnostic systems application is made. A block diagram of the expert diagnostic system operation as well as a scheme of the expert diagnostic system application at an airline enterprise is developed and grounded.